Role of hepatitis C virus in chronic liver disease occurring after orthotopic liver transplantation. Issue 5 (May 1995) - Pastore, M; Willems, M; Cornu, C; Buts, J P; Reding, R; de Ville de Goyet, J; Rahier, J; Otte, J B; Yap, S H; Sokal, E M
Abstract : Paediatric orthotopic liver transplant recipients may develop chronic hepatitis after surgery. To investigate the role of hepatitis C virus in this pathology a cohort of 249 paediatric orthotopic liver transplant recipients was studied. Sixteen children (6.4%) were found to have chronic hepatitis C virus hepatitis after orthotopic liver transplantation. All but one of them had serum transaminase values which were persistently raised two to eight times the upper limit of normal. Thirteen were positive for both serology and serum hepatitis C virus RNA. Serum hepatitis C virus RNA detection occurred five to 33 months before hepatitis C virus antibodies. Liver tissue hepatitis C virus RNA and hepatitis C virus core antigen were detected in five. In one patient, tissue hepatitis C virus core antigen was detected when other tests for hepatitis C were negative. Two patients had positive human cytomegalovirus serum antibodies and RNA before transplantation. Although serum hepatitis C virus RNA was not detected after transplantation, serum enzyme immunosorbent assay and tissue core antigen were still detectable in both patients. In another child, serum hepatitis C virus RNA was positive and hepatitis C virus core antigen was found on a liver biopsy specimen but antihepatitis C virus antibodies were negative as well as liver hepatitis C virus RNA. No patient developed severe liver disease or cirrhosis during a follow up of up to 72 months. It is concluded that hepatitis C virus is a significant cause of morbidity after paediatric orthotopic liver transplantation. Diagnosis cannot rely on serological testing only. The patients remained stable on follow up, but longer prospective histological studies remain necessary to establish prognosis.